2017
DOI: 10.1016/j.heliyon.2017.e00271
|View full text |Cite
|
Sign up to set email alerts
|

Polytopic vaccination with a live-attenuated dengue vaccine enhances B-cell and T-cell activation, but not neutralizing antibodies

Abstract: Dengue, caused by dengue viruses (DENVs), is the most common arboviral disease of humans. Several dengue vaccine candidates are at different stages of clinical development and one has been licensed. Inoculation with live-attenuated DENV constructs is an approach that has been used by vaccine developers. Unfortunately, the simultaneous injection of all four attenuated DENV serotypes (DENV1-4) into a single injection site (monotopic vaccination) has been postulated to result in interference in the replication of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Subunit vaccines are potential substitutes for the current live attenuated dengue virus vaccine approved by the World Health Organization 9 . A recently published study found that this live attenuated vaccine stimulated B and T cells but did not increase production of neutralizing antibodies 13 . We combined these four epitopes into a polytope to create a candidate vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subunit vaccines are potential substitutes for the current live attenuated dengue virus vaccine approved by the World Health Organization 9 . A recently published study found that this live attenuated vaccine stimulated B and T cells but did not increase production of neutralizing antibodies 13 . We combined these four epitopes into a polytope to create a candidate vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…These live attenuated vaccines have associated risks because pathogens are used as the vaccinating agent. One recent study found that injection of polytopic live attenuated dengue virus enhanced B- and T-cell activation, but failed to lead to neutralizing antibody production 13 . Subunit viral proteins also have potential for use in vaccines.…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 , 29 Comparison of polytopic and monotopic Dengue vaccination in NHP showed that while single-site vaccination resulted in more rapid cytokine production, durability was higher in NHP vaccinated via polytopic, separated antigen delivery. 30 Murine studies have also demonstrated the ability to overcome immunodominance by separating vaccine antigens across several anatomic sites. 31 , 32 , 33 , 34 It was recently shown that co-administration of DNA and protein HIV vaccines as fractional polytopic delivery in NHP elicited higher immune responses and offered greater protection from SIV than separating the DNA and protein to contralateral sites.…”
Section: Introductionmentioning
confidence: 99%